Inventions that changed the world - Maule, David (Harlow, England : Penguin Books, 2005)
Inventors are special people. They see everyday objects and imagine something better. They solve problems with new ideas. Their inventions can help people or destroy them, but only the greatest ideas will change the world. This book tells about many of the most interesting and important inventions, from 2,500 years ago to the present day -- p. 4 of cover
Printing -- Mathematics -- Navigation -- Guns -- Engines -- Flight -- Communication -- Computers -- Ideas
Some inventions are so important that they have changed human history. This book looks at some of the most significant inventions from ancient times to the present day, including developments within printing, mathematics, navigation, weapons, flight, communications and computers. Explores these innovations and the impact they have had on our world and our lives
Keywords: Readers (Elementary); Inventions -- History